2014
DOI: 10.1038/ncomms5123
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of nitriles using non-noble metal oxides-based nanocatalysts

Abstract: (Hetero)aromatic and aliphatic nitriles constitute major building blocks for organic synthesis and represent a versatile motif found in numerous medicinally and biologically important compounds. In general, these nitriles are synthesized by traditional cyanation procedures using toxic cyanides. With respect to green chemistry, the development of more sustainable and cost-efficient processes for the synthesis of advanced nitriles is highly desired. Here we report an environmentally benign synthesis of all kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
159
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(164 citation statements)
references
References 35 publications
1
159
1
2
Order By: Relevance
“…The shortest and highly atom-economic route towards biobased amines is the direct coupling of lignin-derived alcohols with ammonia, producing water as the only by-product. However, only a few homogeneous and heterogeneous catalytic methods are known to yield amines 30,31 or nitriles 32 Nature Catalysis directly and the efficiency of these is largely limited by the structure of the substrate. We have found that a versatile building block, nitrile 4, can be obtained through direct transformation of 1G with ammonia using commercially available Ni/ SiO 2 -Al 2 O 3 .…”
Section: Nature Catalysismentioning
confidence: 99%
“…The shortest and highly atom-economic route towards biobased amines is the direct coupling of lignin-derived alcohols with ammonia, producing water as the only by-product. However, only a few homogeneous and heterogeneous catalytic methods are known to yield amines 30,31 or nitriles 32 Nature Catalysis directly and the efficiency of these is largely limited by the structure of the substrate. We have found that a versatile building block, nitrile 4, can be obtained through direct transformation of 1G with ammonia using commercially available Ni/ SiO 2 -Al 2 O 3 .…”
Section: Nature Catalysismentioning
confidence: 99%
“…Hence, merging rationally-designed suitable modified supports with cheap transition metals permits access to the design of active, selective and cheap catalytic materials thus allowing to match or to outperform noble-metal-based catalysts. During the last three years, some of us reported the preparation of active and selective NGr-decorated Co-based catalysts from the pyrolysis of in situ generated 1,10-phenanthroline (Phen) metal complexes using Vulcan® XC 72 R carbon [52][53][54][55][56][57][58][59][60], ceria [61] or α-alumina as supports [62]. Some of the obtained nanoscale catalysts exhibit a core-shell architecture in which a Co metallic core is enveloped by an oxidic sheath composed of Co3O4.…”
Section: Introductionmentioning
confidence: 99%
“…Organic nitriles have been commercially used as common building blocks for high-performance rubbers, polymers and molecular electronics, and are integral parts for producing pharmaceuticals, agrochemicals and fine chemicals, such as vitamins, heterocycles and various carboxylic acid derivatives1234. In 2010, more than 20 additional nitrile-containing pharmaceuticals have been developed in clinical application, demonstrating the greatly important role of organic nitriles5.…”
mentioning
confidence: 99%
“…Metal-catalysed direct ammoxidation has been regarded as a sustainable strategy for producing nitriles due to the significant advantage in avoidance of toxic cyanides1268910111213. In these cases, much success has been achieved by employing primary alcohols, aldehydes and aldoximes as precursors for the formation of C-N bonds1101112.…”
mentioning
confidence: 99%